Influenza outbreak in India: A course ahead - Saxena, Vartika; Mishra, Ashutosh (Indian Journal of Community Health, 2023)
“Influenza” is commonly known as “flu” caused by a single-stranded RNA virus. There are four types of Influenza viruses A, B, C and D, of which type A and B are mainly known to cause respiratory tract infection in humans, especially during the winter and post-monsoon season. It is transmitted rapidly through infectious droplets in crowded places, including schools and hospitals.[1] The incubation period of influenza ranges from1 to 4 days with its period of communicability ranges from one day before the onset of symptoms to 7 days after the symptoms begin.[2] It has already caused multiple pandemics in the past, with a recent one in year 2009 was caused by the Influenza subtype A H1N1 variant (pdm09). Millions of deaths have occurred during these pandemics. The vulnerable population like under-five children, elderly people (? 65years of age), pregnant women, and people with comorbidity like diabetes, chronic kidney disease, chronic obstructive pulmonary disease, chronic heart disease, chronic liver disease and immunocompromised conditions (i.e., HIV/ AIDS, malignancy, individuals on chemotherapy or steroid) are at higher risk of developing severe illness due to infection by Influenza viruses.